The Effectiveness of Schema Therapy on Health Anxiety and Health Stubbornness of People Visiting Neurology Clinics - Alizade Moghaddam, Arezo; Vaslehchi, Tahmineh; Azimi Takami , Zahra; Azimi Takami , Fatemeh; Kiani , Sakineh (Health Nexus, 2024)
The purpose of this research was to determine the effectiveness of schema therapy on health anxiety and health stubbornness of people referring to neuropsychiatric clinics. The research method was semi-experimental and in terms of methodology, it was a pre-test-post-test type. The statistical population included adults who referred to neurology clinics in Sari city in the first three months of 1401. The sample of the research was 30 people who referred to the neurology clinics, who were selected as available, and then they were randomly selected into the experimental group and the control group, and 15 people were placed in each group. The tools of data collection were health anxiety and health stubbornness questionnaires. Then the subjects of the experimental group received 10 sessions of 120 minutes of schema therapy. The findings showed that the mean scores of the variables of health anxiety and health stubbornness in the post-test of the experimental group were significant compared to the pre-test. Therefore, schema therapy has been effective on health anxiety and health stubbornness of people referring to neurology clinics.